2008
DOI: 10.1111/j.1365-246x.2007.03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain accumulation along an oblique plate boundary: the Reykjanes Peninsula, southwest Iceland

Abstract: S U M M A R YWe use annual GPS observations on the Reykjanes Peninsula (RP) from 2000 to 2006 to generate maps of surface velocities and strain rates across the active plate boundary. We find that the surface deformation on the RP is consistent with oblique plate boundary motion on a regional scale, although considerable temporal and spatial strain rate variations are observed within the plate boundary zone. A small, but consistent increase in eastward velocity is observed at several stations on the southern p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 36 publications
(65 reference statements)
3
41
0
Order By: Relevance
“…The 10 km long Vogar fissure swarm lies in the northern portion of the 35 km long and 5–8 km wide Reykjanes fissure swarm, in southern Iceland (Figures a and b) [ Gudmundsson , ; Villemin and Bergerat , ; Clifton and Kattenhorn , ]. The amount of pure extension in this highly oblique portion of rift is ~6 mm/yr [ Keiding et al ., ]. The Vogar fissure swarm consists of a 3–4.5 km wide asymmetric deformation zone delimited on the western edge by an east facing normal fault (Hrafnagjá) and on the eastern edge by a series of open fissures (Grindavikurgjá) [ Villemin and Bergerat , ].…”
Section: Resultsmentioning
confidence: 99%
“…The 10 km long Vogar fissure swarm lies in the northern portion of the 35 km long and 5–8 km wide Reykjanes fissure swarm, in southern Iceland (Figures a and b) [ Gudmundsson , ; Villemin and Bergerat , ; Clifton and Kattenhorn , ]. The amount of pure extension in this highly oblique portion of rift is ~6 mm/yr [ Keiding et al ., ]. The Vogar fissure swarm consists of a 3–4.5 km wide asymmetric deformation zone delimited on the western edge by an east facing normal fault (Hrafnagjá) and on the eastern edge by a series of open fissures (Grindavikurgjá) [ Villemin and Bergerat , ].…”
Section: Resultsmentioning
confidence: 99%
“…Hreinsdóttir et al (2001) suggested a temporal partitioning of strain in which left-lateral shear strain is being accommodated during the current "amagmatic" period, and propose that extensional strain is accommodated during magmatic episodes. The most recent GPS data (Keiding et al 2008) call into question the component of subsidence toward the plate boundary axis, and reveal both a major component of shear and a lesser component of extension across the plate boundary. While all of these recent measurements indicate that the RP is currently accommodating more shear than extension, the majority of surface structures are NE striking extensional features.…”
Section: Reykjanes Peninsulamentioning
confidence: 98%
“…Annual campaign style GPS measurements have been conducted in the SISZ since June 2000 (Árnadóttir et al, ; Decriem et al, ; Juncu et al, ; Keiding et al, ). Figure shows the network of campaign benchmarks and continuously operating GPS stations in South Iceland.…”
Section: Gps Data and Analysismentioning
confidence: 99%